A multidimensional analysis of two registers of English for Navy submariners - Yolanda Noguera Díaz (Universitat Jaume I. Department of English Studies, 2022)
This research explores the differences and similarities found in two corpora representative of two registers of relevance for Navy submariners in the Spanish Navy Submarine Warfare School. It shows cases in a range of analyses based on multi-dimensional analysis that can inform professional language teaching in such contexts. It is argued that linguistic variation among the texts affords the identification of both converging and diverging patterns of variation across dimensions of use.